MBOAT7-TMC4 rs641738 Is Not Associated With the Risk of Hepatocellular Carcinoma or Persistent Hepatitis B Infection - Wang, Peng; Li, Ying; Li, Lu; Zhong, Rong; Shen, Na (Frontiers in Oncology, 2021)
Objective: A hot genetic variant, rs641738 within the membrane-bound O-acyltransferase domain containing 7(MBOAT7) and transmembrane channel-like 4 (TMC4), was recently reported to be associated with several liver diseases. However, the results remain controversial. Therefore, this study aimed to explore the role of MBOAT7-TMC4 rs641738 in the risk of hepatocellular carcinoma (HCC) and persistent hepatitis B virus (HBV) infection. Methods: We first conducted a case-control study that included 779 HCC cases and 1412 cancer-free controls. Controls consisted of 678 persistent HBV carriers and 734 spontaneously recovered subjects. The gene variant rs641738 was genotyped using the MassARRAY platform. The results were analyzed in five genetic models using multivariate logistic regression analyses. Next, we performed a systematic review and meta-analysis to further explore the role of this variant in HCC risk. Results: The results suggested no association between MBOAT7-TMC4 rs641738 and HCC risk in most genetic models (all P > 0.05). Although a marginally significant association was observed in TT vs. CC (P = 0.037) and the recessive models (P = 0.044). The meta-analysis of 2135 HCC cases and 4388 controls supported that this variant was not related to HCC risk, even in the TT vs. CC and recessive models. We also determined that this variant did not influence persistent HBV infection. Conclusion: Our work highlights that MBOAT7-TMC4 rs641738 is not associated with the risk of HCC or persistent HBV infection. This study provides some clues to identify the “truth” of potential disease-related genetic factors in the post-genome era.